Efficacy and safety of sedation with dexmedetomidine in adults undergoing gastrointestinal endoscopic procedures: systematic review and meta-analysis of randomized controlled trials - Tang, Rou; Huang, Yaqun; Zhang, Yujia; Ma, Xiaolei; Yu, Haoyang; Song, Kaichao; Ren, Ling; Zhao, Bin; Wang, Lulu; Zheng, Wensheng (Frontiers in Pharmacology, 2023)
Background: The sedative role of dexmedetomidine (DEX) in gastrointestinal endoscopic procedures is unclear. We performed this systematic review and meta-analysis to assess the efficacy and safety of sedation with DEX during gastrointestinal endoscopic procedures with a view to providing evidence-based references for clinical decision-making. Methods: The PubMed, Embase, Cochrane Library, Web of Science, and ClinicalTrials.gov databases were searched for randomized controlled trials (RCTs) that compared DEX with different sedatives comparators (such as propofol, midazolam, and ketamine) for sedation in a variety of adult gastrointestinal endoscopic procedures from inception to July 1, 2022. Standardized mean difference (SMD) and weighted mean difference (WMD) with 95% confidence interval (CI) or pooled risk ratios (RR) with 95% CI were used for continuous outcomes or dichotomous outcomes, respectively, and a random-effect model was selected regardless of the significance of the heterogeneity. Results: Forty studies with 2,955 patients were assessed, of which 1,333 patients were in the DEX group and 1,622 patients were in the control (without DEX) group. The results suggested that the primary outcomes of sedation level of DEX are comparable to other sedatives, with similar RSS score and patient satisfaction level, and better in some clinical outcomes, with a reduced risk of body movements or gagging (RR: 0.60; 95% CI: 0.37 to 0.97; P=0.04; I2=68%), and a reduced additional requirement for other sedatives, and increased endoscopist satisfaction level (SMD: 0.41; 95% CI: 0.05 to 0.77; P=0.03; I2=86%). In terms of secondary outcomes of adverse events, DEX may benefit patients in some clinical outcomes, with a reduced risk of hypoxia (RR:0.34; 95% CI: 0.20 to 0.55; P<0.0001; I2=52%) and cough (RR: 0.25; 95% CI: 0.12 to 0.54; P=0.0004; I2=0%)), no significant difference in the risk of hypotension, while an increased risk of bradycardia (RR: 3.08; 95% CI: 2.12 to 4.48; P<0.00001; I2=6%). Conclusion: This meta-analysis indicates that DEX is a safe and effective sedative agent for gastrointestinal endoscopy because of its benefits for patients in some clinical outcomes. Remarkably, DEX is comparable to midazolam and propofol in terms of sedation level. In conclusion, DEX provides an additional option in sedation for gastrointestinal endoscopic procedures.